Perancangan Sistem Monitoring Konsumsi Listrik Dan On/Off Stop Kontak Pada Smarthome Dengan Media Komunikasi Bluetooth Low Energy - Bisma Surya Mahendra; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
1,084 kWh / capita is the large amount of electricity use in Indonesia in 2019. Efforts to determine electricity consumption and control of electrical equipment require technology with monitoring and control functions on / off of electrical equipment. By implementing a smart home system it can reduce user efforts in carrying out these activities. To carry out monitoring and control activities, a wireless sensor network is needed to connect users and electrical equipment. One of the JSN communication modules is Bluetooth low energy (BLE). Implementation of the system using ESP32 as a server that supports BLE. Data acquisition is carried out by 2 ACS712 sensors and a ZMPT101B sensor. 2 relay modules as switches and the nRF Connect application as a place client. Users use the client application for monitoring and control of electrical equipment. Testing is done to see system performance. In functional testing all system functions can run smoothly. Testing the accuracy of the voltage and current sensors get results with an error value of 1.23% and 22.93% and the second sensor gets an average error percentage of 29.33%. The client server pairing test got an average time of 0.763ms in the distance scenario and 0.704ms in the closed room scenario. The success of the system in testing with a packet delivery ratio parameter of 75% in each scenario. Performance testing with round trip time parameters obtained the smallest RTT value of 0.00728ms at a distance of 5 meters. And RTT in a closed room scenario is obtained with the smallest time at position A of 0.0064ms. The time for data transmission will be longer if the distance between the client and server is getting farther. The maximum system connection distance is 15 meters.